Profile of person with disabilities in the work market in São Carlos-SP - Aline Aparecida Veltrone; Maria Amélia Almeida (Universidade Federal de Santa Maria (UFSM), 2010)
The insertion of people with disabilities in the job world can be considered one way for social inclusion. In Brazil, there is legislation to support the insertion and permanence of people with disabilities in the job market. The studies done about this issue, demonstrate correlation between level of schooling, professional qualification and insertion condition. However, it would be important to identify how different types of disabilities are related with these variables. The aim of this research was to characterize the insertion of people with disabilities in the job market related to the level of schooling, professional qualification and present occupation. The participants were 92 employees with different disabilities from four companies located in the city of São Carlos-SP with more than 100 employees each. The data collection procedures involved a questionnaire with open and closed questions and the data was analyzed in a quantitative way. The results evidenced that the professional insertion of people with disabilities is done according to the rules of the present job market, such as: schooling level, productivity and competition.